Efficacy of Lycopodium Clavatum, Berberis Vulgaris and Sarsaparilla, in treatment of Urolithiasis of various types (size varying from - 6-12mm) – An Observational Study (Homoeopathy for All, 2025)
What’s New in Kidney Stone  Research Posted on June 5,  2012 by KidneyStoners.org At the 2012 American Urological  Association Annual Meeting,  researchers from around the world  present research on a range of  urological topics, including the  latest information on stone disease,  prevention, and treatment. This year  the meeting was in Atlanta, Georgia  between May 19th and May 23rd,  2012. Drs. Jonathan Shoag and  Brian Eisner presented their  study, “Kidney stone prevalence is  increasing in the United States over  the last 2 decades: a comparison  of NHANES III and NHANES  2007-2008.” The researchers used  a national survey to determine the  percentage of Americans reporting  a history of stones.They found  that compared to data from 1988- 1994, Americans in 2007 to 2008  were much more likely to report  a history of stones. Overall, 8.5%  of Americans report having stones  in 2007-8 compared to 5.2% in  1988-1994. Among men, the current  percentage is 10.6% while it is 6.4%  in women. The increases in stones  was seen for all racial groups.
Keywords: Association; interventional trial; carbonate pills